Land use management: problems of protection of basic national wealth - Novakovskyi, L.; Ievsiukov, Т.; Novakovska, I. (Land Management, Cadastre and Land Monitoring, 2022)
The Ukrainian people, with the votes of 90.3% of those who took part in the All-Ukrainian referendum on December 1, 1991 in support of the Declaration of Independence of Ukraine, confirmed their right to land established by the Declaration of State Sovereignty of Ukraine. According to the Constitution of Ukraine, land is recognized as the main national wealth, which is under special protection of the state.The State Committee of Ukraine for Land Resources was established in 1992 of , which was directly subordinated to the Cabinet of Ministers and implemented the state policy in the field of land relations was carried out by the said central executive body.Beginning in 2000, the State Committee was transformed into the State Agency, which in 2008 was reorganized into the State Committee, then returned to its previous name, and in 2014 was transformed into the State Service of Ukraine for Geodesy, Cartography and Cadastre (State Geocadastre). For the latter body, the powers to implement state policy in the field of geospatial data infrastructure, topographic, geodetic and cartographic activities instead of implementing state policy in the field of land relations became decisive.Land relations are public relations concerning the possession, use and disposal of land. They are represented by a separate branch of law - land, which belongs to its profiling branches. This branch exists in direct connection with the basic (fundamental) branches of law that regulate primary social relations. Topographic, geodetic and cartographic activities, the sphere of national infrastructure of geospatial data do not belong to land relations. The activities of the State Agency have been directed and coordinated by five Ministries for 17 years. The implementation of state policy in the field of land relations has become a secondary task for the second body.The purpose of the studyis to analyze the process of transformation of public authorities on the formation and implementation of state land policy, its impact on land use in the state and justification of directions and ways to preserve the main national wealth.It is established that imperfection in the field of land use and protection management and the lease model of agricultural land use have deprived the economic motivation to introduce soil protection technologies in production, due to which most of the soil cover is in pre-crisis condition. A stable negative balance of humus, nitrogen, phosphorus, and potassium has been formed in agroecosystems.That was recognized as an urgent comprehensive program to neutralize challenges and threats in the environmental sphere, the National Security and Defense Council adopted a decision on this issue in March 2021.The paper focuses on the reference to state control of land use, supports the idea of improving the content of land monitoring and the procedure for its conduct, suggests ways to increase the role of state bodies in improving the land management systemKey words: land use management, land protection, land relations, land management, land monitoring, soil fertility.